Lawsonia inermis Linn; Review of Plant with Both Industrial and Medicinal Properties - Abdulfatai, Aremu; Ayotunde, Oridupa Olayinka (Universitas Airlangga, 2022)
Plants are very important in the global settings, both human and animals make use of them for food and medicinal activities. More than 75% of the entire world populace makes use of plants for their medicinal activities due to the fact that plants have fewer side effects and possess higher degree of synergism when compare to synthetic chemotherapeutic agents. Reports showed that modern synthetic chemotherapeutic drugs have their origin from various medicinal plants. Lawsonia inermis is one of the most important medicinal plants in use. This plant has been in existence several decades ago as drugs, cosmetics and preservative in many cultures and tribes across the globe especially India and Africa. This plant has been prescribed in African alternative therapy as purgatives, abortifacient and astringent. Henna plant has also been reported for some pharmacological potentials which includes; pain reliever, anti-diabetes, liver protective, immune booster, antioxidant, anticancer, anti-inflammatory and inhibiting action against microbes, fungal, viral, trypanosome and plasmodium. There is a belief in India that when Lawsonia inermis is mixed with vinegar, it can serve as a remedy for headaches. It is also used as a coagulant when there is an open wound. In addition, when a poultice is made from the leaves of Lawsonia inermis, it is reported to soothe burns and certain types of eczema. Henna as a medicinal plant is now considered as a valuable source of distinct natural phytochemicals for development of potential new drugs against various diseases in both human and animals.